Cognitive and Motor Impairment Severity Related to Signs of Subclinical Wernicke’s Encephalopathy in HIV Infection - LE BERRE, Anne-Pascale (J Acquir Immune Defic Syndr, 2019)
BACKGROUND: Wernicke’s encephalopathy (WE) is a neurological condition resulting from thiamine deficiency. Although commonly associated with alcoholism, non-alcoholic WE has been described in individuals with Human Immunodeficiency Virus (HIV) infection, but subclinical WE may be underdiagnosed. The current study questioned whether presence of subclinical WE signs underlies cognitive and motor deficits in HIV individuals as observed in alcoholism. SETTING: 56 HIV positive individuals (HIV+) and 53 HIV negative controls (HIV−) were assessed on 6 cognitive and motor domains: attention/working memory, production, immediate and delayed episodic memory, visuospatial abilities, and upper limb motor function. METHODS: Based on a rating scheme by Caine et al, HIV+ individuals were categorized by subclinical WE risk factors (dietary deficiency, oculomotor abnormality, cerebellar dysfunction, and altered mental state). Performance was expressed as age- and education-corrected Z-scores standardized on controls. RESULTS: Sorting by Caine criteria yielded 20 HIV+ as Caine 0 (i.e., meeting no criteria), 22 as Caine 1 (i.e., meeting one criterion), and 14 as Caine 2 (i.e., meeting two criteria). Comparison among HIV+ Caine subgroups revealed a graded effect: Caine 0 performed at control levels, Caine 1 showed mild to moderate deficits on some domains, and Caine 2 showed the most severe deficits on each domain. CONCLUSION: This graded severity pattern of performance among Caine subgroups suggests that signs of subclinical WE can partly explain the heterogeneity in HIV-related cognitive and motor impairment. This study highlights the utility of Caine criteria in identifying potential causes of HIV-related neurocognitive disorders and has implications for disease management.